Misclassifying Core Expenses as Special Items: Cost of Goods Sold or Selling, General, and Administrative Expenses? - Fan, Yun; Liu, Xiaotao (Kelvin) (Contemporary Accounting Research, 2017)
Abstract Prior studies of classification shifting in the income statement conclude that managers misclassify core expenses as special items to inflate reported core earnings (McVay 2006; Fan, Barua, Cready, and Thomas 2010). These studies do not distinguish between the core expense components—cost of goods sold ( COGS ) and selling, general, and administrative expenses ( SGA ). This study models COGS and SGA separately, and investigates managers’ misclassification of COGS versus SGA to meet different profitability benchmarks. We find that COGS (but not SGA ) misclassification is associated with just beating the benchmark of gross margin four quarters earlier. In comparison, both COGS and SGA misclassification are associated with just beating the benchmarks of zero core earnings, prior‐year core earnings, and analyst earnings forecasts in the fourth fiscal quarter. We also investigate real activities management ( RAM ) of COGS and SGA to meet benchmarks, and find that managers engage in RAM of COGS to achieve the gross margin benchmark, but not core earnings benchmarks. We demonstrate that unexpected SGA contains a significant misclassification effect distinct from RAM , suggesting that future RAM research should consider controlling for expense misclassification. Overall, our study extends prior literature on both classification shifting and RAM .